2018
DOI: 10.2217/fca-2017-0068
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Coronary Bifurcation Lesions: Current Knowledge and Future Perspectives

Abstract: Coronary lesions at bifurcation sites are frequent and still remain a challenging subset for the interventional cardiologist. Although in the last years the provisional stenting technique has shown more consistent results, coronary bifurcation interventions still share a worse procedural success rate and increased rates of mid- and long-term cardiac events. Most of the dedicated devices proposed in the last few years have failed to show improved results when compared with standard devices. The broader use of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…In contrast, a thorough registry of patients treated with crossover stenting from LM to the left anterior descending (LAD) branch indicated that the 5year cumulative incidence of TLR was not significantly different between the kissing balloon and non-kissing balloon groups (22). Therefore, the appropriate management of coronary bifurcation lesions remains debatable, especially with LM true bifurcations (23). Drug-coated balloon are emerging devices with established efficacy in ISR, de novo, and small vessels that may provide potential advantages in bifurcation PCI and circumvent the restrictions encountered with this group of lesions (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a thorough registry of patients treated with crossover stenting from LM to the left anterior descending (LAD) branch indicated that the 5year cumulative incidence of TLR was not significantly different between the kissing balloon and non-kissing balloon groups (22). Therefore, the appropriate management of coronary bifurcation lesions remains debatable, especially with LM true bifurcations (23). Drug-coated balloon are emerging devices with established efficacy in ISR, de novo, and small vessels that may provide potential advantages in bifurcation PCI and circumvent the restrictions encountered with this group of lesions (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a thorough registry of patients treated with crossover stenting from LM to the left anterior descending (LAD) branch indicated that the 5-year cumulative incidence of TLR was not significantly different between the kissing balloon and non-kissing balloon groups ( 22 ). Therefore, the appropriate management of coronary bifurcation lesions remains debatable, especially with LM true bifurcations ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Coronary bifurcation lesions are a complex subset of lesions due to several factors: plaque location, plaque burden, branch diameter, branch angle, bifurcation site and the presence of more than two branches. In addition, PCI of coronary bifurcation lesions may also cause anatomical changes (plaque displacement or dissection) ( 4 , 17 ). These unique structural and bifurcation lesion characteristics can be altered and become even more complicated during and after PCI ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Coronary bifurcation lesions are involved in 15–20% of cases of percutaneous coronary intervention (PCI), which is difficult for interventional cardiologists to address ( 1 , 2 ). PCI for bifurcation lesions is a challenging technique and has more procedural complications, a higher restenosis rate and worse clinical outcomes ( 3 , 4 ). The optimal interventional therapy strategy for bifurcation lesions remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Coronary bifurcation disease was the lesion with severe stenosis in the MV and SB, respectively or together [11]. True bifurcation lesions referred to the ones in which both the MV and SB were affected and corresponded to Medina classi cation 1.1.1, 1.0.1, and 0.1.1 [12].…”
Section: De Nitionmentioning
confidence: 99%